Community led testing among people who inject drugs: A community centered model to find new cases of HIV and Hepatitis C in Nepal. - Rajesh Didiya (Public Library of Science (PLoS), 2021)
Background People who inject drugs (PWIDs) have sub-optimal HIV and HCV testing as the available testing services are inadequate in low and middle-income countries. We examined a model of Community-Led Testing (CLT) in Nepal, exploring the feasibility of HIV and HCV testing by trained lay service providers who had similar backgrounds to those of PWIDs. We also assessed the prevalence of HIV and HCV within this study population and the associated risk factors among PWIDs. Methods A mix-methods cross-sectional study was conducted among 1029 PWIDs in five major districts of Nepal from July 2019 to February 2020. Trained PWID peers performed the screening for HIV and HCV using Rapid Diagnostic Test (RDT) kits. Acceptability and feasibility of the testing was assessed. The participants' sociodemographic characteristics and injecting and non-injecting risk characteristics were determined. The association of risk and prevention characteristics with testing results were assessed using multiple logistic regression. Results PWIDs shared that the test providers were friendly and competent in counseling and testing. Of total PWIDs (n = 1,029), 20.6% were HCV-positive and 0.2% were HIV-positive. HCV positivity was associated with needle sharing (AOR: 1.83, 95% CI: 1.27,2.64; p = 0.001) and reuse of syringe/needle (AOR: 2.26; 95% CI: 1.34, 3.79; p = 0.002). In addition, PWIDs were more likely to be HCV-positive who started opioid substitution therapy (OST) (AOR: 1.88, 95% CI: 1.26, 2.80, p = 0.002) and attended the rehabilitation center (AOR: 1.66, 95% CI: 1.10, 2.53, p = 0.017). Conclusions This CLT model was found to be a novel approach of testing of HIV and HCV which was acceptable to PWIDs in Nepal and showed the high prevalence of HCV and its association with injecting-related risk behaviors and being users of OST and rehabilitation. The findings highlight the need of community-led testing in hotspots, OST settings, and rehabilitation centers to screen new HIV and HCV infections.